The comparison of various foam polymer types in composite sandwich panels subjected to full scale air blast loading - Kelly,M; Arora,H; Dear,JP (Procedia Engineering, 2014)
Full scale air blast testing has been performed on a range of polymeric foam composite panels. These panels employed glass fibre reinforced polymer (GFRP) face-sheets with different polymer foam cores, namely: Styrene acrylonitrile (SAN); Polyvinylchloride (PVC) and Polymethacrylimide (PMI). The three sandwich panels were all subjected to 100 kg TNT equivalent blast loading at a stand-off distance of 15 m, and the responses of the panels were measured using Digital Image Correlation (DIC). The extent of damage in the sandwich panels was then inspected via post-blast sectioning, and it was found that the SAN core suffered the least damage, and the PMI suffered the most. The DIC showed that the deflection of the SAN core sandwich panel was much less than the other two foam polymer cores, due to less damage meaning a greater stiffness was retained. All blast research to date is part of a programme sponsored by the Office of Naval Research (ONR).